2020
DOI: 10.1371/journal.pone.0234172
|View full text |Cite
|
Sign up to set email alerts
|

When are researchers willing to share their data? – Impacts of values and uncertainty on open data in academia

Abstract: Background E-science technologies have significantly increased the availability of data. Research grant providers such as the European Union increasingly require open access publishing of research results and data. However, despite its significance to research, the adoption rate of open data technology remains low across all disciplines, especially in Europe where research has primarily focused on technical solutions (such as Zenodo or the Open Science Framework) or considered only parts of the issue. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 77 publications
(156 reference statements)
0
22
0
Order By: Relevance
“…At the time, only a few were involved with projects where opening the data was under consideration. As evidenced also by other authors (Mann et al, 2008;Andreoli-Versbach and Mueller-Langer, 2014;Stieglitz et al, 2020), a certain resistance to openly share the data was present, at least at the beginning. These resistances were mainly due to the concern about the proper acknowledgment to the data producers and the extra time needed to follow and accomplish the whole process (Digital Science et al, 2020).…”
Section: Opening To Scientists Across Time and Spacementioning
confidence: 57%
See 1 more Smart Citation
“…At the time, only a few were involved with projects where opening the data was under consideration. As evidenced also by other authors (Mann et al, 2008;Andreoli-Versbach and Mueller-Langer, 2014;Stieglitz et al, 2020), a certain resistance to openly share the data was present, at least at the beginning. These resistances were mainly due to the concern about the proper acknowledgment to the data producers and the extra time needed to follow and accomplish the whole process (Digital Science et al, 2020).…”
Section: Opening To Scientists Across Time and Spacementioning
confidence: 57%
“…The scientific community seems now ready to implement Open Science in its routine work. However, despite its significance to research, in Europe, the adoption rate of open data technology remains low across all disciplines (Stieglitz et al, 2020). By contrast, some United States (US) governmental institutions (e.g., NASA, NOAA, and USGS), took effort to the application of Open Science principles in the past decades especially on the open data front (e.g., data releases by the ASTER NASA program since 2000 5 , including oceanography data by the NOAA Sentinel Site program 6 ), allowing the use of open data to become common practice at government level, long before similar applications occurred in Europe.…”
Section: Introductionmentioning
confidence: 99%
“…On the contrary, they are not familiar with basic terms of ORD, like FAIR principles and they opposed to any exploitation of their research data for commercial and non-commercial use. This somewhat contradicting perception is mostly related to the competition for career progression or/and the inside knowledge for inconsistencies at the research methodology [61] [25]. In addition, especially for health sciences, it may also be related to the personal (sensitive) character of the medical research data, which demands compliance with medical data protection policies, and it is reflected as well as in participants' responses in the present survey.…”
Section: Resultsmentioning
confidence: 79%
“…Considering data sharing, researchers are generally well aware of personal benefits, like career or performance advantages, even if the degree to which benefits arise varies in relation to disciplines and hierarchy levels [22]. Then again, nevertheless, a systematic review in the field of health and medical research revealed that there are in fact few evidence-based incentives for data sharing, with open data badges being the only tested incentive.…”
Section: Which Kind Of Incentives?mentioning
confidence: 99%